Sown alfalfa pasture decreases grazing intensity while increasing soil carbon: Experimental observations and DNDC model predictions - Xu, Lijun; Ye, Liming; Nie, Yingying; Yang, Guixia; Xin, Xiaoping; Yuan, Bo; Yang, Xiufang (Frontiers in Plant Science, 2022)
Grasslands are the most important land use in China and have experienced extensive degradation in the past few decades due to overgrazing. However, regionally viable solutions to grazing intensity alleviation remained elusive to date. Here, we evaluated the grazing intensity effects of sown alfalfa pastures in northern China using an experiment-modeling combined approach that involved six sites in field experiments and five provinces in DNDC modeling of sown alfalfa pasture’s forage production and carbon sequestration potentials in marginal lands. Our results showed that the sown alfalfa pasture’s dry-matter yield varied between 4.5 and 9.0 t ha-1 under rainfed and irrigated conditions, respectively, from 2025 to 2035. If half of the available marginal lands were mobilized for alfalfa forage production, these yield levels meant that livestock grazing intensity on natural grasslands may drop 8-13% under rainfed and 20-33% under irrigated conditions. Our results also showed that marginal land’s soil organic carbon contents were systematically higher under sown alfalfa pasture than under fallow management by a big margin of 8.5 and 9.9 g kg-1 (i.e., +79 and +95%), under rainfed and irrigated conditions, respectively, during 2025-2035. Overall, these results demonstrated that sown alfalfa pasture on marginal lands represents an effective grassland conservation pathway over the short- to medium-term time horizon based on current technologies.